MATH SOLVE

5 months ago

Q:
# Help plz and explain

Accepted Solution

A:

Given x, y, a, b are positive numbers

[tex]x^{-2/3}=a^{-2}=>x^{-1/3}=\pm{a^{-1}}=>x^{-1/3}=a^{-1}........[x,a >0][/tex]

[tex]y^{2/3}=b^4=>y^{1/3}=\pm{b^2}=>y^{1/3}=b^2..........[y,b >0][/tex]

[tex](xy)^{-1/3}=x^{-1/3}*y^{-1/3}[/tex]

[tex]=x^{-1/3}*y^{-1/3}[/tex]

[tex]=a^{-1}*b^{-2}[/tex]

[tex]=\frac{1}{ab^2}[/tex].

[tex]x^{-2/3}=a^{-2}=>x^{-1/3}=\pm{a^{-1}}=>x^{-1/3}=a^{-1}........[x,a >0][/tex]

[tex]y^{2/3}=b^4=>y^{1/3}=\pm{b^2}=>y^{1/3}=b^2..........[y,b >0][/tex]

[tex](xy)^{-1/3}=x^{-1/3}*y^{-1/3}[/tex]

[tex]=x^{-1/3}*y^{-1/3}[/tex]

[tex]=a^{-1}*b^{-2}[/tex]

[tex]=\frac{1}{ab^2}[/tex].